Real-time cytotoxicity assay of water extracts Hibiscus rosa-sinensis - Nur Husnina Iffah, Bakar; Thong, Chuan Lee; Mohd Hairul, Ab. Rahim; Raha, Ahmad Raus; Dayang Fredalina, Basri; Noor Suhana, Adzahar (Trans Tech Publications, 2020)
A real-time impedance-based electrochemistry assay was used for assessing the cytotoxicity effect of water extract Hibiscus Rosa-Sinensis on Vero cell line. In this study, H. rosa-sinensis was extracted by using the water extraction with three different concentration which were 200, 100 and 50 µg/mL. The phytochemical compounds in the extract were analyzed by using the Gas Chromatography-Mass Spectrometry (GC-MS). The GC-MS result showed that the extract contains bioactive compounds such as n-hexadecanoic acid, pentadecanoic acid, phenol, 2,4-bis(1,1-dimethylethyl) and octadecanoic acid that have bioactive properties such as cytotoxic and antioxidant. The cytotoxic effect of the extract on normal cell line was assessed by using Real-Time Cell Analysis (RTCA) instrument. The result showed that there was no significant cytotoxicity effect against Vero cell lines. This result showed that the real-time impedance-based assay can be utilized to monitor changes of the cells and to determine the inhibitory concentration of the extract.